KNOWLEDGE AND ATTITUDES OF EMERGENCY NURSES REGARDING MEDICATION ERRORS - NAEEM, A; BATOOL, S; AFZAL, F (Biological and Clinical Sciences Research Journal, 2024)
Medication errors in emergency departments can lead to significant patient harm. Understanding the knowledge and attitudes of healthcare professionals regarding these errors is critical for developing effective prevention strategies. Objective: To assess the knowledge and attitudes of emergency department nurses regarding medication errors. Methods: A descriptive, cross-sectional study was conducted in the Emergency Department of Sheikh Zayed Hospital, Rahim Yar Khan, from March 2023 to March 2024. A total of 150 nurses participated in the study. Data were collected using a 43-item questionnaire available in both Urdu and English. The questionnaire comprised six sections, focusing on knowledge, attitudes, and behaviors regarding medication errors. Responses were recorded on a Likert scale ranging from 1 (totally disagree) to 5 (totally agree). Statistical analysis included descriptive statistics to summarize the responses. Results: The mean age of the nurses was 43.6 ± 16.6 years, with 70% being female and 30% male. A majority of nurses agreed that medication errors can be reduced by calculating drug dosages beforehand (76%), using prepackaged drugs from the pharmacy (62%), and utilizing informative brochures and guidebooks (66%). Attitudes towards error reduction were positive, with recommendations for systematic training of healthcare staff (94%), raising awareness about risk management and prevention (90%), evaluating staff for eligibility (90%), and the importance of reporting and assessing errors (94%). Conclusion: Nurses in the emergency department possess sufficient knowledge and exhibit positive attitudes toward medication errors in the management and administration of IV drugs. However, ongoing training programs and awareness initiatives are essential to update nurses’ knowledge and enhance patient safety.